Magnesia carbon brick for electric furnace and preparation method thereof
By using boron nitride powder to spray modified graphite and nanocarbon fiber-modified phenolic resin in magnesia-carbon bricks for electric furnaces, the problems of reduced thermal shock stability and slag permeability resistance of magnesia-carbon bricks are solved, and the service life is significantly extended.
Patent Information
- Application Number
- CN202411512502.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-21
AI Technical Summary
The reduction in carbon content in existing electric furnace magnesium carbon bricks leads to a decrease in thermal shock stability and slag resistance and shorten service life.
Modified graphite is sprayed with boron nitride powder to form a stable boron nitride protective layer, which is combined with nanocarbon fiber-modified phenolic resin to enhance the thermal shock stability and slag permeability resistance of the material.
The thermal shock stability and slag permeability resistance of magnesia carbon bricks are significantly improved, and the service life is extended.
Smart Images

Figure BDA0005105817190000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnesia carbon brick preparation, and in particular to magnesia carbon bricks for electric furnaces and a preparation method thereof. Background Art
[0002] Magnesia-carbon brick for electric furnace is a refractory product made of magnesia and graphite as the main raw materials and is specially used for electric furnaces. This brick has the characteristics of high refractoriness, high corrosion resistance, excellent heat spalling resistance and high temperature volume stability, as well as high thermal shock resistance, which makes it widely used in the furnace wall, lining and slag line of the ladle of electric furnace. However, as the carbon content in magnesia-carbon brick decreases, its thermal shock stability and slag permeability resistance will also decrease accordingly. This will make magnesia-carbon bricks more vulnerable to damage at high temperatures and slag lines, shortening their service life. Summary of the invention
[0003] In view of the defects of the prior art, the object of the present invention is to provide a magnesia carbon brick for an electric furnace and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution:
[0005] The present invention provides a magnesia carbon brick for an electric furnace, which comprises the following raw materials in parts by weight:
[0006] 60-80 parts of fused magnesia, 8-12 parts of modified graphite, 2-4 parts of binder, and 1-1.5 parts of antioxidant, wherein the modified graphite is prepared by spraying graphite with boron nitride powder.
[0007] As a further technical solution of the present invention, the following raw materials are included by weight:
[0008] 70 parts of fused magnesia, 12 parts of modified graphite, 3 parts of binder, and 1.2 parts of antioxidant.
[0009] As a further technical solution of the present invention, the preparation method of the modified graphite comprises:
[0010] The graphite is cleaned with an acetone solvent having a mass fraction of 6 to 8%, and the cleaned graphite is dried at 50 to 80°C for 10 to 30 minutes;
[0011] Adding boron nitride powder into the spraying equipment, so that the spraying distance is 30-40 cm and the coating thickness is 10-20 μm, wherein the particle size of the boron nitride powder is 300-500 nm and the particle size of the graphite is between 0.088 mm and 1 mm;
[0012] The sprayed graphite is placed in a heat treatment furnace, and the heat treatment temperature is 800-900° C., the heat treatment time is 3-5 hours, and the heat treatment is performed under a protective atmosphere; after the heat treatment is completed, it is naturally cooled to room temperature to obtain modified graphite, wherein the protective atmosphere is one of nitrogen or argon.
[0013] In the present invention, a stable boron nitride protective layer can be formed on the graphite surface by spraying modified graphite with boron nitride powder. This protective layer can reduce the oxidation and decomposition of graphite at high temperatures, thereby maintaining the thermal conductivity and stability of graphite. In electric furnace magnesium carbon bricks, this modified graphite can enhance the thermal shock stability of the material, making it more durable in high temperature environments. The modified graphite is added to the electric furnace magnesium carbon bricks, and the boron nitride protective layer on the surface of the modified graphite can serve as an effective barrier to block the penetration of slag liquid. This can not only reduce the erosion of slag liquid on magnesium carbon bricks, but also extend the service life of magnesium carbon bricks.
[0014] As a further technical solution of the present invention, the binder is a modified phenolic resin.
[0015] As a further technical solution of the present invention, the preparation method of the modified phenolic resin comprises:
[0016] Pretreatment of nanocarbon fibers: Slowly add nanocarbon fiber powder to a pre-prepared mixed acid solution, stirring while adding to ensure that the nanocarbon fibers are fully in contact with the mixed acid. The particle size of the nanocarbon fiber powder is between 30nm and 100nm, and the volume ratio between the nanocarbon fiber powder and the mixed acid solution is 1:5-10. React at room temperature for 40-90min, wherein the mixed acid is composed of nitric acid and sulfuric acid in a volume ratio of 3:2, the concentration of nitric acid is 14.5mol / L, and the concentration of sulfuric acid is 18mol / L.
[0017] The pretreated nano-carbon fibers are added to a phenolic resin, the phenolic resin is a phenolic resin of model 2130 produced by Hengtong Chemical Industry Bank in Zhengzhou Economic and Technological Development Zone, the mass ratio between the pretreated nano-carbon fibers and the phenolic resin is 1:50-100, and the mixture is stirred at a stirring speed of 1500-2000 rpm for 1-3 hours, the stirred nano-carbon fiber-modified phenolic resin is injected into a mold, and a curing reaction is carried out at 180-190°C, the curing temperature is 60-120 minutes, and a modified phenolic resin is obtained.
[0018] In the present invention, the uniform dispersion of carbon nanofibers in phenolic resin can form a stable network structure. When the modified phenolic resin is added to electric furnace magnesia carbon bricks as a binder, the carbon nanofibers and boron nitride modified graphite powder are intertwined to form a more dense carbon network structure. This structure helps to improve the overall strength and thermal shock resistance of the material.
[0019] As a further technical solution of the present invention, the fused magnesia is composed of large-particle fused magnesia with a particle size of 3 to 5 mm, medium-particle fused magnesia with a particle size of 1 to 3 mm, micro-particle fused magnesia with a particle size of 0.088 to 1 mm, and small-particle fused magnesia with a particle size of less than 0.088 mm in a mass ratio of 1 to 2:1 to 3:1 to 2:1.
[0020] As a further technical solution of the present invention, the antioxidant is aluminum powder, and the particle size of the aluminum powder is 400-500 mesh.
[0021] Another object of the embodiment of the present invention is to provide a method for preparing magnesia carbon bricks for electric furnaces, comprising the following steps:
[0022] Mix the fused magnesia evenly, then add the modified graphite and binder and stir at a stirring speed of 60-80r / min for 5-8 minutes, then add the antioxidant and stir and continue stirring for 8-10 minutes;
[0023] The mixed materials are squeezed into shape under a press with a pressure of 800 to 1000 tons to form bricks;
[0024] The brick is heat treated at a temperature of 180 to 200° C. for 8 to 12 hours to obtain a magnesia carbon brick for an electric furnace.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention provides a magnesium carbon brick for an electric furnace and a preparation method thereof. In the present invention, graphite is spray-modified by using boron nitride powder to form a stable boron nitride protective layer on the graphite surface. This protective layer can reduce the oxidation and decomposition of graphite at high temperatures, thereby maintaining the thermal conductivity and stability of graphite. In the magnesium carbon brick for an electric furnace, this modified graphite can enhance the thermal shock stability and slag permeability resistance of the material, making it more durable in a high temperature environment. In addition, the present invention uses a phenolic resin modified with nano-carbon fibers on the basis of using modified graphite. The uniform dispersion of nano-carbon fibers in the phenolic resin can form a stable network structure, and the nano-carbon fibers can also be interwoven with the boron nitride modified graphite powder to form a denser carbon network structure. Thereby, the overall strength and thermal shock resistance of the material can be further improved. DETAILED DESCRIPTION
[0027] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The present invention provides a magnesia carbon brick for an electric furnace, comprising the following raw materials in parts by weight:
[0029] 60-80 parts of fused magnesia, 8-12 parts of modified graphite, 2-4 parts of binder, and 1-1.5 parts of antioxidant, wherein the modified graphite is prepared by spraying graphite with boron nitride powder.
[0030] In the embodiment of the present invention, the following raw materials are preferably included in parts by weight:
[0031] 70 parts of fused magnesia, 12 parts of modified graphite, 3 parts of binder, and 1.2 parts of antioxidant.
[0032] In an embodiment of the present invention, the method for preparing the modified graphite comprises:
[0033] The graphite is cleaned with an acetone solvent having a mass fraction of 6 to 8%, and the cleaned graphite is dried at 50 to 80°C for 10 to 30 minutes;
[0034] Adding boron nitride powder to a spraying device, which may be a high-pressure sprayer or a flame sprayer, so that the spraying distance is 30-40 cm and the coating thickness is 10-20 μm, wherein the particle size of the boron nitride powder is 300-500 nm and the particle size of the graphite is between 0.088 mm and 1 mm;
[0035] The sprayed graphite is placed in a heat treatment furnace, and the heat treatment temperature is 800-900° C., the heat treatment time is 3-5 hours, and the heat treatment is performed under a protective atmosphere; after the heat treatment is completed, it is naturally cooled to room temperature to obtain modified graphite, wherein the protective atmosphere is one of nitrogen or argon.
[0036] In the embodiment of the present invention, the binder is a modified phenolic resin.
[0037] In an embodiment of the present invention, the preparation method of the modified phenolic resin comprises:
[0038] Pretreatment of nanocarbon fibers: Slowly add nanocarbon fiber powder to a pre-prepared mixed acid solution, stirring while adding to ensure that the nanocarbon fibers are fully in contact with the mixed acid. The particle size of the nanocarbon fiber powder is between 30nm and 100nm, and the volume ratio between the nanocarbon fiber powder and the mixed acid solution is 1:5-10. React at room temperature for 40-90min, wherein the mixed acid is composed of nitric acid and sulfuric acid in a volume ratio of 3:2, the concentration of nitric acid is 14.5mol / L, and the concentration of sulfuric acid is 18mol / L.
[0039] The pretreated nano-carbon fibers are added to a phenolic resin, the phenolic resin is a phenolic resin of model 2130 produced by Hengtong Chemical Industry Bank in Zhengzhou Economic and Technological Development Zone, the mass ratio between the pretreated nano-carbon fibers and the phenolic resin is 1:50-100, and the mixture is stirred at a stirring speed of 1500-2000 rpm for 1-3 hours, the stirred nano-carbon fiber-modified phenolic resin is injected into a mold, and a curing reaction is carried out at 180-190°C, the curing temperature is 60-120 minutes, and a modified phenolic resin is obtained.
[0040] In the embodiment of the present invention, the fused magnesia is composed of large-particle fused magnesia with a particle size of 3 to 5 mm, medium-particle fused magnesia with a particle size of 1 to 3 mm, micro-particle fused magnesia with a particle size of 0.088 to 1 mm, and small-particle fused magnesia with a particle size of less than 0.088 mm in a mass ratio of 1 to 2:1 to 3:1 to 2:1.
[0041] In the embodiment of the present invention, the antioxidant is aluminum powder, and the particle size of the aluminum powder is 400-500 mesh.
[0042] Another object of the embodiment of the present invention is to provide a method for preparing magnesia carbon bricks for electric furnaces, comprising the following steps:
[0043] Mix the fused magnesia evenly, then add the modified graphite and binder and stir at a stirring speed of 60-80r / min for 5-8 minutes, then add the antioxidant and stir and continue stirring for 8-10 minutes;
[0044] The mixed materials are squeezed into shape under a press with a pressure of 800 to 1000 tons to form bricks;
[0045] The brick is heat treated at a temperature of 180 to 200° C. for 8 to 12 hours to obtain a magnesia carbon brick for an electric furnace.
[0046] Example 1.
[0047] The present invention provides a magnesia carbon brick for an electric furnace, comprising the following raw materials in parts by weight:
[0048] 62 parts of fused magnesia, 8 parts of modified graphite, 2.3 parts of binder and 1 part of antioxidant, wherein the modified graphite is prepared by spraying graphite with boron nitride powder.
[0049] In this embodiment, the preparation method of the modified graphite includes:
[0050] The graphite was cleaned with 6% acetone solvent, and the cleaned graphite was dried at 60°C for 20 minutes;
[0051] Add boron nitride powder into the spraying equipment so that the spraying distance is 30 cm and the coating thickness is 15 μm;
[0052] The sprayed graphite is placed in a heat treatment furnace, the heat treatment temperature is 800°C, the heat treatment time is 3 hours, and the heat treatment is performed under a protective atmosphere; after the heat treatment is completed, it is naturally cooled to room temperature to obtain modified graphite, wherein the protective atmosphere is argon.
[0053] In this embodiment, the binder is a modified phenolic resin.
[0054] In this embodiment, the preparation method of the modified phenolic resin includes:
[0055] Pretreatment of nanocarbon fibers: Slowly add nanocarbon fiber powder to the pre-prepared mixed acid solution, stirring while adding to ensure that the nanocarbon fibers are fully in contact with the mixed acid. The volume ratio between the nanocarbon fiber powder and the mixed acid solution is 1:8. React at room temperature for 70 minutes. The mixed acid is composed of nitric acid and sulfuric acid in a volume ratio of 3:2, the concentration of nitric acid is 14.5 mol / L, and the concentration of sulfuric acid is 18 mol / L.
[0056] The pretreated nanocarbon fibers are added to the phenolic resin, the mass ratio between the pretreated nanocarbon fibers and the phenolic resin is 1:60, and the mixture is stirred at a stirring speed of 1500 rpm for 2 hours. The stirred nanocarbon fiber-modified phenolic resin is injected into a mold, and a curing reaction is carried out at 18°C. The curing temperature is 90 minutes to obtain a modified phenolic resin.
[0057] In this embodiment, the fused magnesia is composed of large-particle fused magnesia with a particle size of 3 to 5 mm, medium-particle fused magnesia with a particle size of 1 to 3 mm, micro-particle fused magnesia with a particle size of 0.088 to 1 mm, and small-particle fused magnesia with a particle size of less than 0.088 mm, in a mass ratio of 1.5:2:1.5:1.
[0058] In this embodiment, the antioxidant is aluminum powder, and the particle size of the aluminum powder is 400-500 mesh.
[0059] Another object of the embodiment of the present invention is to provide a method for preparing magnesia carbon bricks for electric furnaces, comprising the following steps:
[0060] Mix the fused magnesia evenly, then add the modified graphite and binder and mix and stir at a stirring speed of 60r / min for 5 minutes, then add the antioxidant and stir and mix, and continue stirring for 8 minutes;
[0061] The mixed materials are squeezed into shape under a press with a pressure of 1,000 tons to form bricks;
[0062] The brick is heat treated at 190° C. for 10 hours to obtain a magnesia carbon brick for an electric furnace.
[0063] Example 2.
[0064] The present invention provides a magnesia carbon brick for an electric furnace, comprising the following raw materials in parts by weight:
[0065] 80 parts of fused magnesia, 12 parts of modified graphite, 3.5 parts of binder, and 1.3 parts of antioxidant, wherein the modified graphite is prepared by spraying graphite with boron nitride powder.
[0066] In this embodiment, the preparation method of the modified graphite includes:
[0067] The graphite was cleaned with 8% acetone solvent, and the cleaned graphite was dried at 80°C for 20 minutes;
[0068] Add boron nitride powder into the spraying equipment so that the spraying distance is 30-40 cm and the coating thickness is 15 μm;
[0069] The sprayed graphite is placed in a heat treatment furnace, with the heat treatment temperature being 800° C. and the heat treatment time being 5 hours under a protective atmosphere; after the heat treatment is completed, the graphite is naturally cooled to room temperature to obtain modified graphite, wherein the protective atmosphere is argon.
[0070] In this embodiment, the binder is a modified phenolic resin.
[0071] In this embodiment, the preparation method of the modified phenolic resin includes:
[0072] Pretreatment of nanocarbon fibers: Slowly add nanocarbon fiber powder to the pre-prepared mixed acid solution, stirring while adding to ensure that the nanocarbon fibers are fully in contact with the mixed acid. The volume ratio between the nanocarbon fiber powder and the mixed acid solution is 1:8. React at room temperature for 60 minutes. The mixed acid is composed of nitric acid and sulfuric acid in a volume ratio of 3:2, the concentration of nitric acid is 14.5 mol / L, and the concentration of sulfuric acid is 18 mol / L.
[0073] The pretreated nanocarbon fibers are added to the phenolic resin, the mass ratio between the pretreated nanocarbon fibers and the phenolic resin is 1:60, and the mixture is stirred at a stirring speed of 1500 rpm for 2 hours. The stirred nanocarbon fiber-modified phenolic resin is injected into a mold, and a curing reaction is carried out at 180°C for 90 minutes to obtain a modified phenolic resin.
[0074] In this embodiment, the fused magnesia is composed of large-particle fused magnesia with a particle size of 3 to 5 mm, medium-particle fused magnesia with a particle size of 1 to 3 mm, micro-particle fused magnesia with a particle size of 0.088 to 1 mm, and small-particle fused magnesia with a particle size of less than 0.088 mm, in a mass ratio of 1.5:3:1:1.
[0075] In this embodiment, the antioxidant is aluminum powder, and the particle size of the aluminum powder is 400-500 mesh.
[0076] Another object of the embodiment of the present invention is to provide a method for preparing magnesia carbon bricks for electric furnaces, comprising the following steps:
[0077] Mix the fused magnesia evenly, then add the modified graphite and binder and mix them at a stirring speed of 80r / min for 8 minutes, then add the antioxidant and mix them, and continue stirring for 10 minutes;
[0078] The mixed materials are squeezed into shape under a press with a pressure of 1,000 tons to form bricks;
[0079] The brick is heat treated at 200° C. for 10 hours to obtain a magnesia carbon brick for an electric furnace.
[0080] Example 3.
[0081] The present invention provides a magnesia carbon brick for an electric furnace, comprising the following raw materials in parts by weight:
[0082] 70 parts of fused magnesia, 12 parts of modified graphite, 3 parts of binder, and 1.2 parts of antioxidant.
[0083] In this embodiment, the preparation method of the modified graphite includes:
[0084] The graphite was cleaned with 6% acetone solvent, and the cleaned graphite was dried at 70°C for 20 minutes;
[0085] Add boron nitride powder into the spraying equipment so that the spraying distance is 35 cm and the coating thickness is 15 μm;
[0086] The sprayed graphite is placed in a heat treatment furnace, the heat treatment temperature is 800°C, the heat treatment time is 4 hours, and the heat treatment is performed under a protective atmosphere; after the heat treatment is completed, it is naturally cooled to room temperature to obtain modified graphite, wherein the protective atmosphere is argon.
[0087] In this embodiment, the binder is a modified phenolic resin.
[0088] In this embodiment, the preparation method of the modified phenolic resin includes:
[0089] Pretreatment of nanocarbon fibers: Slowly add nanocarbon fiber powder to the pre-prepared mixed acid solution, stirring while adding to ensure that the nanocarbon fibers are fully in contact with the mixed acid. The volume ratio between the nanocarbon fiber powder and the mixed acid solution is 1:8. React at room temperature for 60 minutes. The mixed acid is composed of nitric acid and sulfuric acid in a volume ratio of 3:2, the concentration of nitric acid is 14.5 mol / L, and the concentration of sulfuric acid is 18 mol / L.
[0090] The pretreated nanocarbon fibers are added to the phenolic resin, the mass ratio between the pretreated nanocarbon fibers and the phenolic resin is 1:60, and the mixture is stirred at a stirring speed of 2000 rpm for 2 hours. The stirred nanocarbon fiber-modified phenolic resin is injected into a mold, and a curing reaction is carried out at 180°C for 100 minutes to obtain a modified phenolic resin.
[0091] In this embodiment, the fused magnesia is composed of large-particle fused magnesia with a particle size of 3 to 5 mm, medium-particle fused magnesia with a particle size of 1 to 3 mm, micro-particle fused magnesia with a particle size of 0.088 to 1 mm, and small-particle fused magnesia with a particle size of less than 0.088 mm, in a mass ratio of 1.5:3:1.5:1.
[0092] In this embodiment, the antioxidant is aluminum powder, and the particle size of the aluminum powder is 400-500 mesh.
[0093] Another object of the embodiment of the present invention is to provide a method for preparing magnesia carbon bricks for electric furnaces, comprising the following steps:
[0094] Mix the fused magnesia evenly, then add the modified graphite and binder and mix and stir at a stirring speed of 70r / min for 8 minutes, then add the antioxidant and stir and mix, and continue stirring for 10 minutes;
[0095] The mixed materials are squeezed into shape under a press with a pressure of 1,000 tons to form bricks;
[0096] The brick is heat treated at 190° C. for 10 hours to obtain a magnesia carbon brick for an electric furnace.
[0097] Comparative Example 1.
[0098] The difference from Example 3 is that the graphite is not modified, and graphite is used instead of modified graphite.
[0099] Comparative Example 2.
[0100] The difference from Example 3 is that the phenolic resin is not modified, and the phenolic resin is used instead of the modified phenolic resin.
[0101] Comparative Example 3.
[0102] The difference from Example 3 is that the graphite and the phenolic resin are not modified at the same time.
[0103] The performance test of the magnesia carbon bricks for electric furnace prepared in Examples 1-3 and Comparative Examples 1-3 was carried out. The test results of the thermal shock resistance times were as follows: after heat treatment at 950°C, the bricks were rapidly cooled by wind, and then a pressure of 0.3MPa was applied to observe whether damage occurred. If no damage occurred, the next test was repeated, and the number of times the bricks were subjected to was counted. The results are shown in Table 1 below:
[0104] Table 1
[0105]
[0106] It can be seen from Table 1 that the magnesia carbon bricks for electric furnaces prepared in the embodiment of the present invention have good thermal shock resistance and slag permeability resistance.
[0107] After the graphite is spray-modified, the slag permeability resistance and thermal shock resistance of the material can be significantly improved. The combined use of modified graphite and modified phenolic resin can effectively improve the overall strength and thermal shock resistance of the material.
[0108] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0109] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. Magnesia carbon bricks for electric furnaces, characterized in that: By weight, it includes the following raw materials: 60-80 parts of fused magnesia, 8-12 parts of modified graphite, 2-4 parts of binder, and 1-1.5 parts of antioxidant, wherein the modified graphite is prepared by spraying graphite with boron nitride powder.
2. The magnesia carbon brick for electric furnace according to claim 1, characterized in that: By weight, it includes the following raw materials: 70 parts of fused magnesia, 12 parts of modified graphite, 3 parts of binder, and 1.2 parts of antioxidant.
3. The magnesia carbon brick for electric furnace according to claim 1, characterized in that: The preparation method of the modified graphite comprises: The graphite is cleaned with an acetone solvent having a mass fraction of 6 to 8%, and the cleaned graphite is dried at 50 to 80°C for 10 to 30 minutes; Add boron nitride powder into the spraying equipment so that the spraying distance is 30-40 cm and the coating thickness is 10-20 μm; The sprayed graphite is placed in a heat treatment furnace, the heat treatment temperature is 800-900°C, the heat treatment time is 3-5 hours, and the heat treatment is performed under a protective atmosphere; after the heat treatment is completed, it is naturally cooled to room temperature to obtain modified graphite.
4. The magnesia carbon brick for electric furnace according to claim 3, characterized in that: The binder is modified phenolic resin.
5. The magnesia carbon brick for electric furnace according to claim 4, characterized in that: The preparation method of the modified phenolic resin comprises: Pretreatment of nanocarbon fibers: Slowly add nanocarbon fiber powder to a pre-prepared mixed acid solution, stirring while adding to ensure that the nanocarbon fibers are fully in contact with the mixed acid. The volume ratio between the nanocarbon fiber powder and the mixed acid solution is 1:5-10. React at room temperature for 40-90 minutes. The mixed acid is composed of nitric acid and sulfuric acid in a volume ratio of 3:2, the concentration of nitric acid is 14.5 mol / L, and the concentration of sulfuric acid is 18 mol / L. The pretreated nano-carbon fibers are added to the phenolic resin, the mass ratio of the pretreated nano-carbon fibers to the phenolic resin is 1:50-100, and the mixture is stirred at a stirring speed of 1500-2000 rpm for 1-3 hours. The stirred nano-carbon fiber-modified phenolic resin is injected into a mold, and a curing reaction is carried out at 180-190° C. The curing temperature is 60-120 minutes to obtain a modified phenolic resin.
6. The magnesia carbon brick for electric furnace according to claim 1, characterized in that: The fused magnesia is composed of large-particle fused magnesia with a particle size of 3-5 mm, medium-particle fused magnesia with a particle size of 1-3 mm, micro-particle fused magnesia with a particle size of 0.088-1 mm, and small-particle fused magnesia with a particle size of less than 0.088 mm, in a mass ratio of 1-2:1-3:1-2:
1.
7. The magnesia carbon brick for electric furnace according to claim 1, characterized in that: The antioxidant is aluminum powder, and the particle size of the aluminum powder is 400-500 meshes.
8. A method for preparing magnesia carbon bricks for electric furnace according to claim 5, characterized in that: The following steps are involved: Mix the fused magnesia evenly, then add the modified graphite and binder and stir at a stirring speed of 60-80r / min for 5-8 minutes, then add the antioxidant and stir and continue stirring for 8-10 minutes; The mixed materials are squeezed into shape under a press with a pressure of 800 to 1000 tons to form bricks; The brick is heat treated at a temperature of 180 to 200° C. for 8 to 12 hours to obtain a magnesia carbon brick for an electric furnace.
Citation Information
Patent Citations
Nanocarbon reinforced low-carbon magnesia carbon brick and preparation method thereof
CN108484130A
Non-oxide composite low-carbon magnesia carbon brick
CN111908898A
Magnesia carbon brick for electric furnace and preparation method thereof
CN115073142A
Cited By
Novel magnesia carbon brick for converter mouth and preparation method thereof
CN120841939A